The Nodule-Specific PLAT Domain Protein NPD1 Is Required for Nitrogen-Fixing Symbiosis . Issue 3 (6th May 2019) - Pislariu, Catalina I.; Sinharoy, Senjuti; Torres-Jerez, Ivone; Nakashima, Jin; Blancaflor, Elison B.; Udvardi, Michael K.
Abstract : A nodule-specific PLAT-domain protein in Medicago truncatula is critical for intracellular accommodation of rhizobia, and is a determinant of host-strain specificity. Abstract: Symbiotic nitrogen fixation by rhizobia in legume root nodules is a key source of nitrogen for sustainable agriculture. Genetic approaches have revealed important roles for only a few of the thousands of plant genes expressed during nodule development and symbiotic nitrogen fixation. Previously, we isolated >100 nodulation and nitrogen fixation mutants from a population of Tnt1 -insertion mutants of Medigaco truncatula . Using Tnt1 as a tag to identify genetic lesions in these mutants, we discovered that insertions in a M. truncatula nodule-specific polycystin-1, lipoxygenase, α-toxin (PLAT) domain-encoding gene, MtNPD1, resulted in development of ineffective nodules. Early stages of nodule development and colonization by the nitrogen-fixing bacterium Sinorhizobium meliloti appeared to be normal in the npd1 mutant. However, npd1 nodules ceased to grow after a few days, resulting in abnormally small, ineffective nodules. Rhizobia that colonized developing npd1 nodules did not differentiate completely into nitrogen-fixing bacteroids and quickly degraded. MtNPD1 expression was low in roots but increased significantly in developing nodules 4 d postinoculation, and expression accompanied invading rhizobia in the nodule infection zone and into the distal nitrogen fixation zone. A functional MtNPD1:GFP fusion protein localized in the space surrounding symbiosomes in infected cells. When ectopically expressed in tobacco ( Nicotiana tabacum ) leaves, MtNPD1 colocalized with vacuoles and the endoplasmic reticulum. MtNPD1 belongs to a cluster of five nodule-specific single PLAT domain-encoding genes, with apparent nonredundant functions.